2022
DOI: 10.1080/21655979.2022.2074666
|View full text |Cite
|
Sign up to set email alerts
|

Long intergenic non-protein-coding RNA 467 promotes tumor progression and angiogenesis via the microRNA-128-3p/vascular endothelial growth factor C axis in colorectal cancer

Abstract: Long non-coding RNAs (lncRNAs) are important regulators and biomarkers of tumorigenesis and tumor metastasis. Long intergenic non-protein-coding RNA 467 (LINC00467) is associated with various cancers. However, the role and mechanism of LINC00467 in colorectal cancer (CRC) promotion are poorly understood. This study aimed to present new details of LINC00467 in the progression of CRC. Reverse transcription–polymerase chain reaction demonstrated that the expression level of LINC00467 in CRC tissues and cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…We and others have previously shown that tumor angiogenesis and tumor migration and invasion ability play crucial roles in CRC development, especially tumor metastasis [ 28 , 29 ]. To further investigate the biological function of LOC101928222 in CRC, we designed a LOC101928222 overexpression vector and shRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously shown that tumor angiogenesis and tumor migration and invasion ability play crucial roles in CRC development, especially tumor metastasis [ 28 , 29 ]. To further investigate the biological function of LOC101928222 in CRC, we designed a LOC101928222 overexpression vector and shRNAs.…”
Section: Resultsmentioning
confidence: 99%